1991
DOI: 10.2527/1991.692719x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibilities of soft winter wheat, improved triticale cultivars, and pearl millet for finishing pigs.

Abstract: A replicated 4 x 4 Latin square digestion trial was conducted to determine apparent nutrient digestibilities and N and energy balances for soft red winter wheat, Beagle 82 triticale, Florico triticale, and pearl millet using finishing pigs fitted with ileal T-cannulas. Fortified experimental diets contained 97.5% of each respective grain. Nitrogen and amino acid digestibilities of soft winter wheat and triticale were similar (P greater than .13) when measured near the end of the small intestine and over the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
6

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 0 publications
2
17
0
6
Order By: Relevance
“…Our CP values were in good agreement with the values reported by Haydon and Hobbs (1991) and Gelaye et al (1997). Burton et al (1972) found that CP content of pearl millet ranged between 88 and 209 g kg…”
Section: Protein Compositionsupporting
confidence: 81%
“…Our CP values were in good agreement with the values reported by Haydon and Hobbs (1991) and Gelaye et al (1997). Burton et al (1972) found that CP content of pearl millet ranged between 88 and 209 g kg…”
Section: Protein Compositionsupporting
confidence: 81%
“…Os CDPB e CDEB do IAPAR-1 mm foram próximos aos registrados (84,4 e 84,8%) por Haydon & Hobbs (1991) e inferiores aos relatados por Fialho et al (1999), para o CDPB (86,20%). Na Tabela 7, estão compilados os dados do Ensaio 1 e do Ensaio 2, para matéria seca digestível (MSD), proteína digestível (PD), energia digestível (ED) e energia metabolizável (EM) dos diferentes milhetos.…”
Section: Resultsunclassified
“…As diferenças observadas na ED, EM, PD e MSD foram similares às citadas na literatura (Haydon & Hobbs, 1991;Adeola & Orban, 1995;Lawrence et al, 1995;Fialho et al, 1999), evidenciando as grandes variações nos valores nutricionais dos diferentes milhetos analisados. Contudo, a não-identificação das variedades dos milhetos estudados nestes trabalhos dificulta a comparação destas diferenças.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A baixa digestibilidade da treonina é consistente com os resultados de outros estudos (Fontes et al,1998;Haydon & Hobbs, 1991) e se deve, provavelmente, à sua alta concentração na mucina da mucosa intestinal (Fuller, 1994). O coeficiente médio de digestibilidade aparente dos aminoácidos essenciais da quirera de arroz foi 81,00%, variando de 65,80% para a treonina a 88,70% para a arginina.…”
Section: Digestibilidade Ileal Aparenteunclassified